Emergency contraceptio: Whichare the available tools? (2020)
The purpose of emergency contraception (EC) is to prevent unplanned pregnancy when there has been unprotected intercourse. It’s a medical strategy that allows birth control, without being a regular method of family planning. Initially was called “morning-after pill”, which was an inadequate definition because it’s not always a pill, it should not be expected the next morning to use it and can be used several days after intercourse. To identify available tool for EC, a literature review was performed in the PubMed, ScienceDirect, EBSCOhost, OvidSP, Embase (English) and Scielo (Spanish) databases. The application of the intrauterine copper device, within the first five days after intercourse, is the most efficient way to perform EC. Similarly, ulipristal acetate is the best way for hormonal EC. The effectiveness rates of levonorgestrel-only pills and those of ethinyl estradiol combined with levonorgestrel (Yuzpe's method) are important, statistically significant and accepted for EC, remembering that dose and timing should be respected when administered. Mifepristone 10 mg, single dose, is approved in Russia, China, Vietnam and Armenia, as EC. Health professionals should advance high quality contraceptive counseling, to offer as plan B any of the above tools to administer EC. Governments should be concerned about the permanent availability of EC. The prescription of EC should be accompanied by sufficient instructions for women to initiate a regular method of birth control.